Одержання та застосування продуктів оксидаційного очищення кам’яного та бурого вугілля - Швед, Марія Євгенівна (Національний університет "Львівська політехніка", 2018)
Дисертаційна робота присвячена розробленню наукових основ технологій оксидаційного знесірчення (очищення) низькометаморфізованого високосірчистого кам’яного вугілля з метою одержання сировини для виробництва пиловугільного палива та бурого вугілля для отримання смоли розкладу його органічної маси, яка може застосовуватись у якості компонентів котельних палив та/або дорожніх бітумів. Встановлено вплив чинників на дані процеси і знайдено їхні оптимальні значення. Для можливості реалізації процесу оксидаційного очищення у промисловості запропоновано універсальну технологічну схему процесу, яка дає змогу очищати (знесірчувати) як кам’яне, так і буре вугілля. Диссертация посвящена разработке научных основ технологий оксидационного обессеривания (очистки) низкометаморфизированных высокосернистых каменных углей с целью получения сырья для производства пылеугольного топлива и бурых углей для получения смолы деструкции его органической массы, которая может применяться в качестве компонентов котельных топлив и/или дорожных битумов. Установлено влияние факторов на данные процессы и найдены их оптимальные значения. Для возможности реализации процесса оксидационной очистки в промышленности предложена универсальная технологическая схема процесса, которая позволяет очищать (обессеривать) как каменный, так и бурый угли. The dissertation is devoted to the development of scientific bases of oxidative desulfurization (purification) technology for low-metamorphosed high-sulfur black coal to obtain raw materials for the production of pulverized coal (PC) as well as for brown coal with the aim of obtaining its organic matter decomposition resin, which may be used as components of fuel oils and/or road bitumen. The influence of processes factors was determined and their optimal values were found. It has been proved that under conditions when the sulfur conversion rate is limited by the oxidant external diffusion (the linear velocity of the oxidant is 10.030-0.042 m/s, the mass transfer coefficient is 1.63-2.13 10-3 m/s), the desulfurized coal fully meeting the requirements for PC may be obtained from the fraction 0.1-0.25 mm. On the basis of experimental results an adequate experimental-statistical model has been developed, with the help of which the optimal conditions for the oxidative desulfurization process of low-metamorphosed coal were established in order to obtain raw materials for the production of pulverized coal: temperature – 430 0С, duration - 15 minutes, oxidant consumption ratio – 5.10 m3/(h kg), the content of water vapor in the oxidant – 47 %v/v. The solid desulfurized fuel obtained under optimal conditions is characterized by the following values: total sulfur content – 1.38 wt.%, ash content – 9.24 wt.%, volatile matter yield – 37.88 wt.%, humidity – 1.16 wt.%. Thus, the obtained product fully meets the requirements for the raw materials to produce PC in accordance with TU U 10.1-30962337-006: 2009. The researches on brown coal oxidative desulfurization have established that the resin of the organic matter decomposition obtained as a result of coal oxidative purification can be used as fuel oil and/or a plasticizer of polymer-modified bitumen. The use of this plasticizer will improve the plastic properties of modified bitumen without decreasing its adhesion and softening temperature. The obtained desulfurized brown coal, in the case of its future burning at the thermoelectric power station, would allow to reduce the environmental pollution by SO2 by 55.52%. In order to implement the oxidative purification process in the industry, an universal technological scheme is proposed, which enables to purify (desulfurize) both black and brown coal.
Получение и применение продуктов оксидационной очистки каменного и бурого углей
Production and application of the products of black and brown coal oxidative purification
Keywords: вугілля; оксидаційне знесірчення; піритна сірка; пиловугільне паливо; органічна маса вугілля; смола розкладу; котельне паливо; пластифікатор; уголь; оксидационное обессеривание; пиритная сера; пылеугольное топливо; органическая масса угля; смола деструкции; котельное топливо; пластификатор; coal; oxidative desulfurization; pyrite sulfur; pulverized coal fuel; coal organic matter; decomposition resin; fuel oil; plasticizer; 502.3:504:5:662.6/74